Organoleptic Test of Durian Seed-Based Salak Seed Kolak - I Putu Arya Getas Kusuma Jaya; Nina Indra Kristiana (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine the quality of durian seed-based salak kolak by boiling and mashing it. The data collection methods used are experimental methods, organoleptic tests, panelists, documentation, questionnaires, and Likert scales. This study was assessed by organoleptic tests tested on 25 fairly trained panelists to determine the organoleptic test of durian seed-based salak kolak seen from the color aspect getting an index value of 89.6% with very good interpretation criteria, in terms of aroma getting an index value of 91.2% with very good interpretation criteria, in terms of taste getting an index value of 90.4% with very good interpretation criteria, in terms of texture getting an index value of 89.6% with very good interpretation criteria, so that the total average result is 90.2% with very good interpretation criteria.